2004
DOI: 10.1111/j.1443-9573.2004.00176.x
|View full text |Cite
|
Sign up to set email alerts
|

Single‐blind follow‐up study on the effectiveness of a symbiotic preparation in irritable bowel syndrome

Abstract: Compared with baseline values and the control group, SCM-III resulted in a significant increase in lactobacilla, eubacteria and bifidobacteria, which suggests that some selected IBS patients could benefit substantially from symbiotics, but the treatment may need to be given on a cyclic schedule because of the temporary modification of the fecal flora.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
70
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(72 citation statements)
references
References 41 publications
1
70
0
Order By: Relevance
“…Two frequently included papers reported studies in children. 49,50 Two were placebo controlled but single-blinded studies, 33,51 one combined acupuncture with probiotic treatment, 46 and one 32 reported microbiota changes from a probiotic trial published before 52 which was already included in our list.…”
Section: Resultsmentioning
confidence: 99%
“…Two frequently included papers reported studies in children. 49,50 Two were placebo controlled but single-blinded studies, 33,51 one combined acupuncture with probiotic treatment, 46 and one 32 reported microbiota changes from a probiotic trial published before 52 which was already included in our list.…”
Section: Resultsmentioning
confidence: 99%
“…In 2004, Tsuchiya et al [35] published data regarding the utility of the symbiotic mixture SCM-III in 68 consecutive adults with IBS. SCM-III contains not only live bacteria (in this case L. acidophilus, L. helviticus, and Bifidobacterium species) but also specific substrates known as prebiotics that improve microbial growth and survival.…”
Section: "Positive" Articlesmentioning
confidence: 98%
“…These studies have included single species (Lactobacillus GG, L. salivarius, L. reuteri and Bifidobacterium infantis) [33,34•,38], probiotic mixtures [35,36], and symbiotic preparations [32,39]. A single study by Bausserman and Michail [38] addresses the use of probiotics for IBS in children.…”
Section: Recent Studiesmentioning
confidence: 99%
“…However, the benefits have been reported to differ among given species, in different clinical studies and by the IBS subtypes. [5][6][7][8][9][10][11][12][13][14][15][19][20][21][22][23] Some organisms exhibit immunomodulatory effects and limited abnormal fermentation in the colon. 24,25 Others have anti-inflammatory effects 26 or enhance the mucosal defense against luminal bacteria by preventing bacterial adherence to the epithelial cell surface, eliminating bacterial translocation and decreasing the increased intestinal permeability.…”
Section: Discussionmentioning
confidence: 99%
“…Lactobacilli, Bifidobacteria, and Streptococci are among the most commonly studied probiotics in IBS; they have demonstrated efficacy in patients with IBS. [5][6][7][8][9][10][11][12][13][14][15] However, the benefits of one given species or organism have not been shown to be better than other species or organisms. Dietary fiber is commonly used in the treatment of patients with IBS.…”
Section: Introductionmentioning
confidence: 99%